THE INFLUENCE OF SENSE EXPERIENCE AND FEEL EXPERIENCE ON TOURISTS' INTENTION TO REVISIT - Dini Herdianti; Eri Novari; Leni Burhan; Layli Rahmawati; Herry Sutanto (JEMBA: Journal of Economics, Management, Business and Accounting, 2023)
This research is motivated by the existence of market openness which results in the number of products in the form of goods and services increasing and causing too many people to compete in the market. One of them is Waterboom Tirta Sumber Jaya Cipangalun, a company engaged in the tourism sector that competes with an emphasis on the loyalty of its visitors so that they have an interest in visiting again by paying attention to important factors in the marketing field such as sense experience and feel experience. The purpose of this study was to determine the effect of sense experience and feel experience on the interest of returning tourists at Waterboom Tirta Sumber Jaya Cipangalun Ciamis partially and simultaneously. The research method used is a descriptive verification method with a quantitative approach. This type of data includes all variables that are closely related to the influence of sense experience and feel experience on the interest of returning tourists. Data collection techniques were obtained from questionnaires and literature studies. The sample used in this study amounted to 100 respondents of tourists from Waterboom Tirta Sumber Jaya Cipangalun Ciamis using a non-probability sampling method. The results of the analysis using multiple linear regression where these results indicate that sense experience and feel experience have a positive and significant effect on the interest of returning tourists. The results of the partial analysis using the t-test showed that for the sense experience variable, tcount > ttable (7.578 > 1.984) with a significance value of 0.000 <0.05. For the feel experience variable, tcount > ttable (4.978 > 1.984) with a significance value of 0.000 <0.05. The results of simultaneous hypothesis testing using the F test showed that the value of Fcount > Ftable (170,204 > 3.09) with a significance value of 0.000 < 0.05. From the calculation of the coefficient of determination (R2), the result is 0.778 or 77.8%. While the remaining 22.2% is influenced by other variables not examined in this study.